IMF Research Bulletin, September 2013. (IMF Research Bulletin; IMF Research Bulletin ;, 2013)
The Research Summaries in the September 2013 IMF Research Bulletin focus on 'External Conditions and Debt Sustainability in Latin America' (Gustavo Adler and Sebastian Sosa) and 'Monetary Policy Cyclicality in Emerging Markets' (Donal McGettigan, Kenji Moriyama, and Chad Steinberg). In the Q and A, Itai Aigur and Sunil Sharma discuss 'Seven Questions on Macroprudential Policy Frameworks.' The Research Bulletin also includes an updated listing of recent IMF Working Papers, Staff Discussion Notes, and Recommended Readings from the IMF Bookstore, as well as information on a forthcoming conference. The IMF Economic Review's new Impact Factor is also highlighted.